2014
DOI: 10.1039/c4ra03048f
|View full text |Cite
|
Sign up to set email alerts
|

High-temperature, high-pressure hydrothermal synthesis, crystal structure and photoluminescent properties, of K3[Gd1−xTbxGe3O8(OH)2] (x = 0, 0.3, 0.1, 1)

Abstract: A family of new lanthanide germanates K3LnGe3O8(OH)2 have been synthesized by a high-temperature, high-pressure hydrothermal method and characterized by single-crystal X-ray diffraction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…From the structural viewpoint, the second ligands in 1−5 only act as connectors between the bicapped sandwich-type {Ln 8 Ge 12 } cage and the supporting Ln 3+ cations, but can't connect neighboring SBUs. Thus, continued increasing the amount of the second ligand, 25 6 was obtained (Fig. 6a−e, S15 in ESI), as we expected, the second pza − ligand links adjacent {Dy 11 Ge 12 }-6 SBUs together.…”
Section: Resultssupporting
confidence: 68%
See 3 more Smart Citations
“…From the structural viewpoint, the second ligands in 1−5 only act as connectors between the bicapped sandwich-type {Ln 8 Ge 12 } cage and the supporting Ln 3+ cations, but can't connect neighboring SBUs. Thus, continued increasing the amount of the second ligand, 25 6 was obtained (Fig. 6a−e, S15 in ESI), as we expected, the second pza − ligand links adjacent {Dy 11 Ge 12 }-6 SBUs together.…”
Section: Resultssupporting
confidence: 68%
“…S3m−o in ESI), which is different from that of capped Nd 3+ cations in the previously reported FJ-19 made by our group. 15 As to the supporting Nd 3+ cation (Nd9 3+ ), it displays the eight-coordinate bicapped trigonal prism geometry defined by three O COO atoms of E groups, 25 two N atoms and two O COO atoms of pza ligands and one terminal water molecule (Fig. S3p−r in ESI).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…9 Since then, Rocha et al have reported a series of lanthanide silicates AV-n (n = 9, 20, 23) 10 22 With continuous interest in the exploratory synthesis of lanthanide silicates under HT and HP conditions, our group has reported a number of microporous lanthanide silicates with special structures. 2,23,24,25 In this work, a new europium silicate, NaEuSi 3 O 7 (OH) 2 , has been prepared under HT and HP conditions, and its structure and luminescence properties have also been systematically investigated.…”
Section: Introductionmentioning
confidence: 99%